PENGARUH PERKAWINAN DI BAWAH UMUR TERHADAP TINGKAT PERCERAIAN DALAM PERSPEKTIF HUKUM ISLAM - Sri Hariati (The Juris, 2022)
The main problem of this research is how is the effect of underage marriage on the rate of divorce in the perspective of Islamic law (case study) in north lombok district? The main problem is further divided into several sub-problems, namely: 1. What are the factors that cause underage marriage in North Lombok Regency. 2. What is the impact caused by divorce by children who marry underage in North Lombok Regency. 3. What is the view of Islamic law on underage marriage? This type of research is classified as field qualitative research (field research) or in legal research it is called empirical research with a syar'i approach. Sources of data obtained from primary data in the form of interviews and secondary data in the form of library research and data collection techniques through interviews, documentation, and literature studies, which were processed and analyzed descriptively qualitatively. The results obtained from this study are: 1. The factors that cause underage marriages in the Gondang sub-district, North Lombok Regency are economic factors, low awareness of the importance of education, parental concerns, and environmental factors where they live. 2. The impact caused by divorce carried out by children who marry underage in Gondang sub-district, North Lombok Regency, is the impact on oneself (experiencing trauma), changes in roles and status, and difficulty in adjusting.